Tremors [videorecording (Blu-Ray)] - Maddock, Brent, 1950-; Wilson, S. S. (Steven S.); Underwood, Ron; Bacon, Kevin, 1958-; Ward, Fred, 1942-2022; Carter, Finn; Gross, Michael, 1947-; McEntire, Reba (Universal Studios Home Entertainment, 2010)
The small desert town of Perfection is under attack from giant prehistoric man-eating worms that can sense any sound. Now the few left alive must get out of town before they end up as worm food.